Parental Role Models in Children's Character Education in the Society 5.0 Era - Muhammad Ichsan Thaib (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2025)
A child's success really depends on the parent's ability to set an example for their child. The current reality, especially in the 5.0 era, is that many parents are no longer role models. The aim of this research is to find out what examples are shown by parents in the 5.0 era. The method in this paper uses library research with a philosophical approach (examining parental example in the 5.0 era). The data collection technique used is documentation techniques. Many parents are inadequate in providing role models for their children. If parents want to be successful, they should educate themselves with a commitment to Islamic teachings, namely by being educated in the faith and always following the Sunnah of the Prophet Muhammad SAW and always being a role model for their children. Because the Messenger of Allah is the best example for all people. Parents who can be imitated can essentially be educators for their children throughout life, even throughout the ages, because their children's example will be passed on to the next generation and so on. Example is the key to success, including the success of parents in educating their children.